Trójgłos o prawniczym pojęciu czynu: [Three views on the legal concept of an act] (Studia Prawnicze / The Legal Studies, 2023)
Autorzy artykułu przedstawiają interpretację pojęcia „czynu” przez różne dyscypliny prawnicze ze szczególnym uwzględnieniem nauki prawa karnego i cywilnego. Celem publikacji jest porównanie znaczenia terminu „czynu” w różnych dyscyplinach oraz innych terminów, które są znaczeniowo zbliżone. Autorzy przedstawiają definicje „czynu” i wskazują na wieloaspektowość tego pojęcia. Zwrócono uwagę fakt, iż żeby w całości zrozumieć sens przepisów, należy wykazać się znajomością nie tylko obowiązującego systemu prawa, lecz także zasobu wiedzy z zakresu innych gałęzi prawa a także poglądów doktryny. The authors of this article present the interpretation of the concept of an “act” by various legal disciplines with a particular focus on criminal and civil law sciences. The objective of the publication is to compare the meaning of the term “act” in different disciplines and other terms that are semantically similar. The authors provide definitions of “act” and point out the multifaceted nature of the concept. Attention is drawn to the fact that, in order to fully understand the meaning of the provisions, it is necessary to demonstrate knowledge not only of the applicable legal system, but also of other branches of law as well as of doctrinal views.